FACTORS AFFECTING CONSUMERS ANALYSIS IN ONLINE SHOP LAZADA PURCHASE DECISIONS (CASE STUDY OF INDONESIAN CHRISTIAN UNIVERSITY FACULTY OF ECONOMICS AND BUSINESS) - Adolf Somar, Jonathan Agustinus; Sembiring , Carolina F. (Universitas Kristen Indonesia, 2021)
Today, with the rapid development of innovation and the web in Indonesia, it has significantly affected business changes, starting from the way to promote, how to buy and offer, how to interact between people and informal long-distance communication work. In this study, the problem to be discussed is how the relationship between service quality promotion prices and purchasing decisions is made. In this study, researchers examined Lazada's online shop. Thegpurpose of this studyiwas to determinejthe effect ofkprice, promotiona, servicejquality on purchasingudecisions at the Lazada online shop. In this study, researchers took a sample of 40 Lazada users to beptested using multipleglinear regressionjanalysis. The final result of the hypothesis in thisjstudy usingmultiple linearjregression analysisgis. 1) Price has no effect on purchasing decisions at Lazada'sionline shop, with a t-count value < t-table, (1,267 < 2.042) This result shows that price has a negative impact on purchasingydecisions.2) Promotionghas an effectaon purchasing decisions at Lazada's online shop, with a value of t-count > t-table, (3.551 > 2.042) These results indicate that promotions have a positive impact on purchasingtdecisions. 3) Service quality has no effect on purchasing decisions at Lazada's online shop. , with arvalue ofgt-count < t-table, (1,338 <2,042) This result shows that quality has a negative impact on purchasing decisions. Keywords : price, service quality, promotion, purchase decision